Ipsilateral, Multi-Phasic Retinal Vascular Events following Intralesional Triamcinolone Acetonide Injection for Earlobe Keloid: A Case Report - Yafeng Li (Case Reports in Ophthalmology)
Introduction: Intralesional triamcinolone acetonide is a widely used treatment for scarring skin conditions such as keloid and is known to have retinal vascular complications if administered in the periocular region. Case Presentation: A 32-year-old female experienced a prompt onset transient vision decrease and a delayed onset, slow-resolving vison loss in the right eye (OD) following the last of a series of triamcinolone acetonide corticosteroid (TAC) injections in her right earlobe for a disfiguring keloid. Clinically, she developed a branch retinal arterial occlusion accompanied by features of a central retinal vein occlusion. The TAC particles that entered the retinal circulation are implicated in the thrombo-embolic occlusion of the branch retinal artery and subsequent blockage of the central retinal vein. Conclusion: This case should alert clinicians that there is always a potential hazard for retinal vascular occlusion when corticosteroid is injected in the region of the head and face because of the rich anastomoses between the external and internal carotid artery circulations.